Role of Artificial Intelligence in Higher Education - Mithraa, A. (Indian Journal of Computer Science, 2026)
Artificial Intelligence (AI) is a technology that has emerged as a revolutionary technology and is transforming the education sector, particularly higher education. Higher education institutions are increasingly using Artificial Intelligence technology to improve the efficiency of teachers and the quality of education. This study aims to find the role of Artificial Intelligence technology in higher education institutions and evaluate the awareness, adoption, and perception of Artificial Intelligence technology by educators and students. The present study is based on primary data that has been collected through structured questionnaires from 100 samples in higher education institutions. Statistical techniques such as simple percentage analysis, mean ranking, and correlation analysis were employed to interpret the findings. The study concludes that the role of Artificial Intelligence technology is significant in improving the quality of education. However, lack of technology, high cost of implementing Artificial Intelligence technology, and data privacy are the key challenges faced by educators in adopting Artificial Intelligence technology in higher education institutions. The study concludes that the role of Artificial Intelligence technology is significant in improving the quality of education in higher education institutions.